Uma análise da transiç\~ao dos jovens para o primeiro emprego no Brasil - Maurício Reis (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This paper investigates Young workers transition from unemployment to first job. Evidence indicates that the probability of getting a job is lower for youths who have never worked before, even when they are compared to those youths with previous labor market experience. Also, time to first job is usually longer considering full-time jobs as well as those in the formal sector. However, estimates show that unemployed youths and adults with previous labor market experience have similar probabilities of getting a job.
Keywords: J64; J60; 330; first job; unemployment duration